Alexithymia as a potential source of symptom over‐reporting: An exploratory study in forensic patients and non‐forensic participants. Issue 2 (19th January 2018) - Merckelbach, Harald; Prins, Chinouk; Boskovic, Irena; Niesten, Isabella; À Campo, Joost
Abstract : The traditional interpretation of symptom over‐reporting is that it indicates malingering. We explored a different perspective, namely that over‐reporting of eccentric symptoms is related to deficits in articulating internal experiences (i.e., alexithymia). Given that alexithymia has been linked to sleep problems and that fatigue may fuel inattentive responding to symptom lists, we administered measures of alexithymia (TAS‐20) and symptom over‐reporting (SIMS), but also sleep quality (SLEEP‐50) to forensic psychiatric outpatients ( n = 40) and non‐forensic participants ( n = 40). Forensic patients scored significantly higher on all three indices than non‐forensic participants. In the total sample as well as in subsamples, over‐reporting correlated positively and significantly with alexithymia, with r s being in the 0.50–0.65 range. Sleep problems were also related to over‐reporting, but in the full sample and in the forensic subsample, alexithymia predicted variance in over‐reporting over and above sleep problems. Although our study is cross‐sectional in nature, its results indicate that alexithymia as a potential source of over‐reporting merits systematic research.